Factors associated with the introduction of complementary feeding in the French ELFE cohort study. Issue 2 (20th October 2017) - Bournez, Marie; Ksiazek, Eléa; Wagner, Sandra; Kersuzan, Claire; Tichit, Christine; Gojard, Séverine; Thierry, Xavier; Charles, Marie‐Aline; Lioret, Sandrine; de Lauzon‐Guillain, Blandine; Nicklaus, Sophie
Abstract: The objectives of this study were to estimate the age of complementary feeding introduction (CFI) and investigate the related health, demographic, and socio‐economic factors. Analyses were based on 10, 931 infants from the French national birth cohort ELFE, born in 2011. Health, demographic, and socio‐economic data concerning infants and parents were collected at birth (face‐to‐face interviews and medical records) and 2 months (telephone interviews). Data on milk feeding and CFI practices were collected at birth and 2 months then monthly from 3 to 10 months using online or paper questionnaires. The associations between both health and social factors and CFI age were tested by multivariable multinomial logistic regressions. The mean CFI age was 5.2 ± 1.2 months; 26% of the infants started complementary feeding before 4 months of age (CF < 4 months), 62% between 4 and 6 months of age, and 12% after 6 months of age (CF > 6 months). CF < 4 months was more likely when mothers smoked, were overweight/obese, younger (<29 years), and used their personal experience as an information source in child caregiving and when both parents were not born in France. CF < 4 months was less likely when the infant was a girl, second‐born, when the mother breastfed longer, and had attended at least one birth preparation class. Mothers of second‐born infants and who breastfed their child longer were more likely to introduce CF > 6 months. Couples in which fathers were born in France and mothers were not born in France were less likely to introduce CF > 6 months. CF < 4 months occurred in more than 25% of the cases. It is important to continue promoting clear CFI recommendations, especially in smoking, overweight, young, not born in France, and nonbreastfeeding mothers.